A comparison of multiple forward somersault dives from the 3m springboard: a case study - Walker, C. A.; Sinclair, P. J.; Cobley, S.; Sanders, R.; Graham, K. S. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The aim of this study was to examine the differences in the angular velocity profiles and key positional angles of multiple forward somersault dives from the 3m springboard. One internationally ranked male diver performed the forward 1½, 2½, 3½ pike (P) dives while a second diver performed the 4½ tuck (T) dive. High speed video footage and inertial measurement units (IMU) were used to determine eight biomechanical variables. Results indicate that the diver performing the 4½T had a 177 deg/s increase in the angular velocity plateau and held onto his somersault position for 0.26s longer when compared to the 3½P. The forward 4½T takeoff angles were similar to those used in the 2½P and 3½P, but were slightly under rotated at entry. The IMUs proved to be a suitable analysis tool for springboard diving coaches wanting quick turnaround™ performance analysis.